Pengaruh Strategi Pembelajaran berbasis E-Learning dan Motivasi Belajar terhadap Prestasi Mata Pelajaran Sejarah Kebudayaan Islam (SKI) - Sri Mulyati; Khoiruddin Nasution (Fahima, 2022)
The purposes of this study are 1) to determine the effect of e-learning learning strategies on the achievement of SKI subjects; 2) to determine the effect of learning motivation on the achievement of SKI subjects; 3) to determine the effect of e-learning based learning strategies and learning motivation on the achievement of SKI subjects. The study used a quantitative approach with a population of 78 students. Data were taken through a questionnaire with validity and reliability tests. Multiple regression techniques analyzed the research data. The research object is MA NU Gesi Sragen students academic year 2020/2021. The results showed that e-learning-based learning strategies and learning motivation positively influenced student achievement in SKI subjects for MA NU Gesi Sragen students in the academic year 2020/2021.